2007
DOI: 10.1556/avet.55.2007.1.10
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of the leaf extract of Harungana madagascariensis Lam. ex Poir. (Hypericaceae) against strains causing otitis externa in dogs and cats

Abstract: Otitis externa in dogs and cats is always caused by a combination of yeasts and bacteria, among which the most important are Malassezia pachydermatis, Staphylococcus intermedius and Pseudomonas species. These organisms often develop resistance to classical antimicrobial agents. Therefore, the aim of this study was to investigate the antimicrobial activities of an ethyl acetate leaf extract of Harungana madagascariensis against the organisms cited, to carry out the phytochemical investigation of this extract an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…10 Documented scientific studies indicate isolation of compounds like anthrones, anthraquinones, xanthones, flavonoids, and essential oils from this plant. [11][12][13] Also, various parts of the plant have been reported to possess antiprotozoan activity, 14 antifungal and antimicrobial activity, [15][16][17] antioxidant and modulatory effect on cyclophosphamide-induced neurotoxicity, 18 as well as acting as antioxidant markers in alloxan-induced diabetic and carrageenan-induced inflammatory disorders in rats. To our knowledge, the levels of minerals, vitamins, antinutrients, acute toxicity, and in vitro antioxidant activity of the stembark of H. madagascariensis have not been reported despite its widespread use.…”
Section: Introductionmentioning
confidence: 99%
“…10 Documented scientific studies indicate isolation of compounds like anthrones, anthraquinones, xanthones, flavonoids, and essential oils from this plant. [11][12][13] Also, various parts of the plant have been reported to possess antiprotozoan activity, 14 antifungal and antimicrobial activity, [15][16][17] antioxidant and modulatory effect on cyclophosphamide-induced neurotoxicity, 18 as well as acting as antioxidant markers in alloxan-induced diabetic and carrageenan-induced inflammatory disorders in rats. To our knowledge, the levels of minerals, vitamins, antinutrients, acute toxicity, and in vitro antioxidant activity of the stembark of H. madagascariensis have not been reported despite its widespread use.…”
Section: Introductionmentioning
confidence: 99%
“…This flavanoid has been reported to show antioxidative [10], insecticidal [11], antibacterial [12], antimicrobial [13] antinociceptive and antiedematogenic [14] activities formerly. Our study has demonstrated its immunosuppressive activities including improvement of immunologic liver injury [15], collagen-induced arthritis [16] and contact hypersensitivity Figure 1 Effect of astilbin on the adhesion of Jurkat cells to fibronectin, type IV collagen, hyaluronate or ECV-304 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the study suggest that the extract could be used as an antimicrobial preparation for OE (Moulari et al . ). A recent open pilot study considered the efficacy of medical grade honey (MGH) in the management of canine OE.…”
Section: Topical Therapy To Manage Secondary Causes Of Otitismentioning
confidence: 97%